Penggunaan Media Pembelajaran dalam Pembelajaran PAI dan Budi Pekerti - Arlina Arlina; Bunga Ulantika; Fitra Khoiron; Juni Tri Iswani; Mhd. Fadliq Ananta (Universitas Muhammadiyah Enrekang, 2023)
Education is the most important part of society. Education is a place for humans to develop science and technology and various other aspects. Education in the era of globalization also has a significant impact on the development of people's mindsets in reading the situations and conditions that occur in a country. Media is part of the learning component, the benefits and functions of media in learning are felt by both educators and students. PAI learning is a learning effort from educators to students to prepare students to be able to believe, understand, live and practice the teachings of Islam. In the learning process there are various components that play a very important role, namely educators, students, and learning materials. Basically, an educator imparts knowledge to his students to increase their understanding of Islam. Learning media is anything that is used to convey information or messages in the learning process or teaching and learning process so that it can stimulate students' attention and interest in learning.